2013
DOI: 10.1136/bmj.f1738
|View full text |Cite
|
Sign up to set email alerts
|

Boldt: the great pretender

Abstract: The withdrawal of almost 90 fraudulent studies by a German anaesthetist is one of the biggest medical research scandals of recent time. Jacqui Wise examines what happened and what lessons have been learnt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 9 publications
1
64
0
8
Order By: Relevance
“…Unfortunately, in 2010, Boldt, who along with his colleagues [9] had made substantial contributions to the debate in favor of colloids, especially HES, was suspended and was charged for scientific misconduct including failure to acquire ethical approval and fabrication of study data in 88 of 102 studies all of which are now withdrawn from medical literature. [10] Unfortunately, the charges against Boldt have multiplied the skeptical view regarding HES; hence, more clinical studies should be undertaken to find reliable answers related to the efficacy of this solution.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in 2010, Boldt, who along with his colleagues [9] had made substantial contributions to the debate in favor of colloids, especially HES, was suspended and was charged for scientific misconduct including failure to acquire ethical approval and fabrication of study data in 88 of 102 studies all of which are now withdrawn from medical literature. [10] Unfortunately, the charges against Boldt have multiplied the skeptical view regarding HES; hence, more clinical studies should be undertaken to find reliable answers related to the efficacy of this solution.…”
Section: Discussionmentioning
confidence: 99%
“…Academic misconduct and subsequent retraction of published research has cut a wide swath through perioperative medicine in recent years. [10][11][12] An investigative journalist highlighted the failures in scientific publishing and peer review when 157 of 255 (61%) open access journals accepted his submission of an entirely fictional and deeply flawed manuscript. 13 A review of contemporary Danish medical practice guidelines found that 43 of the 45 guidelines (96%) had one or more authors with an undeclared conflict of interest related to the pharmaceutical industry.…”
mentioning
confidence: 99%
“…This sort of post-publication peer review was essential to the identification of misconduct in perioperative medicine. 10,12 Finally, the importance of an objective assessment of the breadth of evidence has been voiced by both the Cochrane Collaboration and a recent initiative to replicate key studies in oncology. Funded through the Center for Open Science, the Reproducibility Initiative will offer US$1.3 million to replicate major studies in cancer biology with open access publication of results assured.…”
mentioning
confidence: 99%
See 2 more Smart Citations